Acute and emergency care in athletic training - Cleary, Michelle A. 1970-; Flanagan, Katie Walsh (Human Kinetics, 2020)
Acute and Emergency Care in Athletic Training is an invaluable text for students in athletic training programs. It provides them with the necessary information to examine, treat, and manage common acute injuries and illnesses